PWE-106 Is it necessary for all colorectal cancer patients with liver metastasis to be discussed at a hepatobiliary MDT?. (28th May 2012) - Vasudevan, S; Wright, J; Rees, M; Creswell, B; Stiff, D; Wordley, A; Motson, R
Abstract : Introduction: Current guidelines suggest an opinion from a hepatobiliary MDT should be sought for all patients with colorectal cancer liver metastasis. This places a significant burden of work on the hepatobiliary MDT who are often the referral centre for many hospitals (Approximately 20 cases per month at our referral centre). This study was performed to see if our local colorectal MDT was able to make a correct decision regarding referral for consideration of liver resection by comparing its decision with the decision from two hepatobiliary surgeons from our referral network. Methods: CT scans from 38 patients found to have liver metastasis from colorectal cancer were anonymised and sent to two hepatobiliary surgeons in our cancer network (Pelican Centre, Basingstoke). They classified them into three categories; U—Unresectable, C—Chemo to downstage then consider resection and R—Resectable. The results were then compared with the opinion of our local colorectal MDT made prior to the referral to the hepatobiliary MDT. Results: The two independent hepatobiliary surgeons agreed with each other on 35/38 (92%) of the CT scans. Our CRC MDT agreed with the hepatobiliary surgeons in 36/38 (95%) of cases. Only 6/29 (21%) patients deemed suitable by review of the CT scan by the hepatobiliary surgeons went on to have a liver resection due to a variety of disease and patient factors. Conclusion: Our results show that our local colorectal MDT was able to make an accurate assessment of the need for referral for consideration of liver resection in this group of patients. We question the need for all similar cases to be "automatically" discussed with a hepatobiliary MDT such as those patients with wide spread liver disease. It is clear from the fact that only 21% of suitable patients for liver resection went on to have a resection that the colorectal MDT is making complex decisions based on many other patient factors. Competing interests: None declared.